The Relationship between the Shoulder Functional Score and the Change in Labral Morphology after Arthroscopic Bankart Repair - Temiz, A; Şahbat, Y; Pepe, I M; Aktekin, C N (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2023)
PURPOSE OF THE STUDY: The aim of arthroscopic Bankart repair is restoration of the anterior block mechanism and regaining stability. There are few studies that have tested the adequacy of the angle made with the glenoid and the height from the glenoid level of the repaired labral tissue, but the correlation with the clinical results is not clear. The aim of this study was to defi ne the correlation of the height and slope of the repaired labral tissue in the glenoid anterior with the clinical results. MATERIAL AND METHODS This prospective study included 20 patients who underwent an arthroscopic Bankart repair. To evaluate the labrum anatomy of the affected shoulder, 4 measurement parameters were defi ned as axial height (Ah), axial slope (As), oblique coronal height (Ch), and oblique coronal slope (Cs) on non-contrast T2 MRI. The measurements were taken preoperatively of the affected shoulder and at 1 year postoperatively of both the affected shoulder and the contralateral asymptomatic shoulder. The measured values were compared with each other and with the contralateral shoulder. Correlations of the anatomic values with the Constant-Murley scores recorded at 1, 3, 6, and 12 months postoperatively were examined with the Wilcoxon test. RESULTS The mean preoperative Constant score of the patients was 57.7 (32-77) and postoperative scores at 1, 3, 6, and 12 months were 63.6 (44-79), 77.8 (61-90), 89.6 (77-100), and 95.2 (79-100), respectively (p=0.001). There was a statistically signifi cant difference in the preoperative MRI measurements of the axial and oblique coronal plane labral height and slope values compared to the postoperative values and those of the asymptomatic contralateral shoulder (p< 0.05 for all). There was no statistically signifi cant difference between the labral height and slope values of both planes postoperatively compared to the asymptomatic contralateral shoulder (p= 0.776, p= 0.910, p= 0.132, p= 0.589, respectively). These increases in the radiological data were not found to be statistically signifi cant in the correlation analysis with the increases in the Constant-Murley scores (Ah p=0.935, As p=0.587, Ch p=0.078, Cs p=0.105). CONCLUSIONS This prospective study was conducted using conventional T2 magnetic resonance imaging, which was suffi cient for the measurement of labral height and slope. This study results showed no signifi cant correlation between the radiological and clinical outcomes. KEY WORDS: Bankart repair, labrum height, labrum slope, functional result.
Keywords: Arthroscopy; Scapula; artroskopie; Amputation, Surgical; Humans; prospektivní studie; amputace; Shoulder; Prospective Studies; rameno; lopatka; lidé